Compartmentalization by directional gene expression - Daube, Shirley S. (National Academy of Sciences, 2010)
The coalescence of basic biochemical reactions into compartments is a major hallmark of a living cell. Using surface-bound DNA and a transcription reaction, we investigate the conditions for boundary-free compartmentalization. The DNA self-organizes into a dense and ordered phase with coding sequences aligned at well-defined distances and orientation relative to the surface, imposing directionality on transcription. Unique to the surface in comparison to dilute homogeneous DNA solution, the reaction slows down early, is inhibited with increased DNA density, is favorable for surface-oriented promoters, and is robust against DNA condensation. We interpret these results to suggest that macromolecules (RNA polymerase and RNA), but not solutes (ions and nucleotides), are partitioned between immobilized DNA and the reservoir. Without any physical barrier, a nonequilibrium directional DNA transaction forms macromolecular gradients that define a compartment, thus offering a boundary-free approach to the assembly of a synthetic cell.